Determinants of Nutrition Care Practice by Midwives and Nurses in the Antenatal and Postnatal Care Settings: A Multi-Site Cross-Sectional Survey From Ghana - Jacqueline Kumbiley MSc; Anthony Amalba PhD; Paul Armah Aryee PhD; Simon Agongo Azure MPhil; Victor Mogre PhD (SAGE Publishing, 2021)
Aim. Midwives and nurses are critical in nutrition care for pregnant women and lactating mothers. Ghanaian nurses and midwives' perception of the adequacy and their satisfaction with nutrition education received during training in school, level of nutrition care competencies, and nutrition practice behavior is unknown. We evaluated the adequacy of nutrition education received in nursing and midwifery school; nutrition care competencies; self-efficacy and the nutrition care practice of midwives and nurses. We also evaluated determinants of nutrition care practice during routine antenatal and postnatal care. Methods. Cross-sectional study conducted among midwives and nurses working at antenatal and postnatal clinics in Ghana. Data was collected using a self-administered questionnaire. Data analysis was done using descriptive statistics, correlation, and linear regression. Findings. Almost 90% (n = 267) of the participants received nutrition education during training, 77.5% were unsatisfied with the amount of time allocated for nutrition education and 40% felt inadequately prepared from school to provide nutrition care. Self-efficacy ranged from moderate to low. Determinants of nutrition care practice were age of respondents ( B  = 0.04; P  = .002), nutrition-related knowledge ( B  = 0.05; P  = .016), adequacy of nutrition education ( B  = 0.14; P  = .006), nutrition training after school ( B  = 0.38; P  = .010) and nutrition care self-efficacy ( B  = 0.03; P  = .048). Conclusion. Notable knowledge gaps in basic nutrition, inadequate preparedness, and poor confidence to provide nutrition care was common. There is a need to improve the nutrition education experiences of midwives and nurses through curricula revision and refresher training courses.